(untitled) (Journal of Nepal Geological Society, 2013)
Interseismic strain across the Himalaya is associated with intense microseismic activity. In this study we analyze in detail this seismicity to explore in more details how it relates to Himalayan tectonics. We use the Double Difference Relocation Method to relocate local earthquakes recorded by National Seismological Centre in the period between 1995 and 2003. We also determined fault plane solutions for 10 earthquakes based on waveforms modeling and first P-motion data to complement the existing dataset of focal mechanisms. The results depict a narrow belt of intense seismic activity, at depth between 10 and 20km, which can be traced all along the topographic front of the Higher Himalaya in Nepal. This zone coincides with the zone of interseismic strain build up at the down dip end of the locked portion of the Main Himalayan Thrust fault. These earthquakes probably activate minor faults within the Himalayan wedge, in a volume which experiences stress build up in the interseismic period. The intense seismic activity generally cease abruptly as the elevation of topography gets higher than 3500 m. This elevation also coincides with a change of tectonic regime. Earthquakes within the seismicity belt at front of the Higher Himalaya are of thrust type indicating N-S shortening. Where the topographic elevation is higher than 3500 m focal mechanisms indicate E-W extension. The effect of topography on the regional stress field thus provides a simple explanation for the distribution of focal mechanisms and the seismicity cut-off at the 3500m elevation contour line.